E-Training Penyusunan Karya Tulis Ilmiah Best Practice Bagi Guru dan Kepala Sekolah untuk Meningkatkan Profesionalitas - Sophia Tri Satyawati; Yari Dwikurnaningsih; Bambang Ismanto; Ade Iriani; Wasitohadi Wasitohadi; Marinu Waruwu (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Principals and teachers play a strategic role in improving the quality of education as shown by the best experience (Best Practice) in carrying out their main tasks and functions. Best practices need to be disseminated and published in order to be a reflection and inspiration for others to improve the quality of education. However, the facts show that principals and teachers do not yet have adequate knowledge and skills in compiling best practice scientific papers. This community service activity aims to improve skills in compiling best practice scientific papers for teachers and principals at Private Education Foundations. The training is carried out online with the following methods: lecture, question and answer, discussion, guidance, and performance. The success of community service is shown by: 1) the number of participants exceeding the target of 50 increases to 53 people; 2) attendance reached 92.96% (very good); 3) The increase in the pre test - post test scores reached 76% (Good); 4) The number of training products reached 71.69% (Good) with a product quality score of 77.80 (Good). This success shows the enthusiasm of the participants and very high awareness of the importance of writing best practices for increasing the professionalism of teachers and principals.